A high-temperature alloy ingot, a preparation method thereof and application thereof

CN121204396BActive Publication Date: 2026-10-16UNIV OF SCI & TECH BEIJING
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511321796.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2026-10-16
Estimated Expiration
2045-09-16

AI Technical Summary

Technical Problem

中国专利CN111876651A公开了一种大尺寸高铌高温706合金铸锭及其冶炼工艺,其关注的是制备的高铌高温706合金铸锭是否存在冶金缺陷,用于解决现有冶炼工艺易出现Al、Ti元素烧损严重以及所制得的高铌高温706合金铸锭易出现黑斑和白斑的冶金缺陷的问题

Benefits of technology

(1)本发明首先对返回料进行一次真空感应熔炼并经浇铸得到返回料铸锭,将不同来源、不同种类的返回料熔炼成成分一致的返回料铸锭,检测化学成分后再锯切成块备用,该步骤避免了直接将不同来源、不同形态及不同成分的返回料加入新料时导致的熔体成分波动,成分极难控制,从而能缩短炉前分析时间、加快冶炼节奏,提高合金成分均质化程度,并扩大返回料的可用范围;此外,该步骤能够将返回料中携带的浮渣、夹杂物、杂质元素等可以通过一次真空感应熔炼并经浇铸进行预去除,进而减轻返回料与新料混合熔炼时导致的浮渣、夹杂物和杂质元素去除任务。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121204396B_ABST
    Figure CN121204396B_ABST
Patent Text Reader

Abstract

The application relates to a high-temperature alloy ingot and a preparation method and application thereof, and belongs to the technical field of metallurgy. The method comprises the following steps: vacuum induction melting and casting return materials to obtain return material ingots, detecting components and cutting blocks to obtain return material cut blocks; vacuum induction melting new material stable components and C components to obtain new material melting bodies, stopping power film formation, adding the return material cut blocks into the new material melting bodies for mixed melting, adjusting components by adding new material easy-oxidation components, and casting to obtain vacuum induction ingots; sequentially performing electroslag remelting, primary vacuum consumable remelting and secondary vacuum consumable remelting on the vacuum induction ingots to obtain the high-temperature alloy ingot; the high-temperature alloy ingot prepared by using the return materials contains the return materials with a mass percentage of more than 40%, the total content of O, N and S impurity elements in the ingot is less than 30ppm, the inclusion quantity density is less than 30 / mm 2 , and the mechanical properties of the rod material forged from the ingot are equivalent to those of the new material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallurgical technology, and particularly relates to a high-temperature alloy ingot, its preparation method, and its application. Background Technology

[0002] High-temperature alloys are the cornerstone of advanced aero-engines, widely used in high-temperature hot-end components such as turbine disks, blades, and casings. Their metallurgical quality and performance play a decisive role in improving engine reliability, safety life, and performance. The development needs of next-generation aero-engines have accelerated the development of high-temperature alloys towards high alloying, large size, and low cost. Among these, the addition of recycled materials is the most important way to reduce the cost of high-temperature alloys. In recent years, relevant domestic units have developed various high-temperature alloy recycled material purification technologies through technology introduction and independent research and development, covering the entire process of sorting, cleaning, smelting, and forging. However, the overall level is lagging behind, especially in the utilization rate of waste high-temperature alloys and the level of purification smelting, which still lag behind foreign countries. The use of high-quality, high-proportion recycled materials introduces higher levels of impurity elements and non-metallic inclusions compared to virgin materials. Directly mixing and melting recycled materials with virgin materials will inevitably result in excessive levels of impurity elements and non-metallic inclusions, seriously affecting the metallurgical quality of high-temperature alloys.

[0003] Currently, the production process of high-temperature alloy ingots in my country mainly includes: dual-process smelting, represented by vacuum induction melting (VIM) + electroslag remelting (ESR) or vacuum induction melting (VIM) + vacuum arc remelting (VAR); and triple-process smelting, represented by vacuum induction melting (VIM) + electroslag remelting (ESR) + vacuum arc remelting (VAR), to produce high-quality high-temperature alloy ingots. These ingots are then homogenized and forged into bars, which can then be processed into various finished forgings. Among these, the triple-process smelting, represented by VIM + ESR + VAR, can remove harmful impurities and non-metallic inclusions from high-temperature alloy ingots to the greatest extent possible, reduce segregation, and eliminate metallurgical defects. It is also a key foundation for expanding ingot sizes and preparing large-diameter bars and large-size disc / ring forgings.

[0004] Existing methods for preparing large-size high-temperature alloy ingots only focus on the high-temperature alloy smelting process, segregation level, and metallurgical defects. No reports have been found regarding the use of a high proportion of recycled materials to prepare large-size, high-purity ingots, nor have there been any reports on the levels of impurity and trace element content in the alloy after ingot enlargement. For example, Chinese patent CN114657398A provides a method for preparing a large-size, difficult-to-deform nickel-based high-temperature alloy ingot. This method mainly involves a three-stage process: vacuum induction melting, protective atmosphere electroslag remelting, and vacuum consumable remelting, to obtain a consumable ingot. This three-stage smelting process can produce a difficult-to-deform nickel-based high-temperature alloy consumable ingot with a diameter of Φ660mm, and the resulting consumable ingot has a low degree of dendrite segregation. Its focus is on the high-temperature alloy smelting process and segregation level. Chinese patent CN111876651A discloses a large-size high-niobium high-temperature 706 alloy ingot and its smelting process. It focuses on whether the prepared high-niobium high-temperature 706 alloy ingot has metallurgical defects, and is used to solve the problems of severe burning loss of Al and Ti elements in the existing smelting process and the metallurgical defects of black spots and white spots in the prepared high-niobium high-temperature 706 alloy ingot.

[0005] In summary, it is essential to provide a method for preparing high-purity, large-size high-temperature alloy ingots using recycled materials, as well as their applications. Summary of the Invention

[0006] To address one or more technical problems existing in the prior art, this invention provides a high-temperature alloy ingot prepared using recycled material, its preparation method, and its application. The high-temperature alloy ingot prepared by this invention is a high-purity, large-size ingot prepared using recycled material, with a diameter reaching 660mm~700mm. The recycled material usage ratio can reach over 40%, the total content of O, N, and S impurity elements is less than 30ppm, the total content of 45 trace elements is less than 200ppm, and the inclusion number density is less than 30 inclusions / mm². 2 Furthermore, the prepared high-temperature alloy ingots are forged into bars after undergoing high-temperature homogenization diffusion annealing treatment, and the mechanical properties of the bars are comparable to those of the new material.

[0007] The present invention provides a method for preparing a high-temperature alloy ingot in a first aspect, the method comprising the following steps: (1) The recycled material is vacuum induction melted and cast to obtain a recycled material ingot. The chemical composition of the recycled material ingot is detected and it is cut into pieces to obtain recycled material pieces. (2) Vacuum induction melting of the new material stable components and C components to obtain a new material melt body. Then, power is turned off to form a film and return material blocks are added to the new material melt body for mixing and melting. Then, the chemical composition is adjusted by adding the easily oxidized components of the new material and casting is performed to obtain a vacuum induction ingot. (3) The vacuum induction casting ingot is subjected to electroslag remelting, primary vacuum arc remelting, and secondary vacuum arc remelting in sequence to obtain a high-temperature alloy casting ingot; the high-temperature alloy casting ingot contains more than 40% recycled material by mass, the total content of O, N, and S impurity elements in the high-temperature alloy casting ingot is less than 30 ppm, and the inclusion number density is less than 30 inclusions / mm 2 .

[0008] In a second aspect, the present invention provides a high-temperature alloy ingot prepared by the preparation method described in the first aspect.

[0009] In a third aspect, the present invention provides the application of a high-temperature alloy ingot prepared by the preparation method described in the first aspect of the present invention in the preparation of bars or ring forgings.

[0010] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The present invention first performs vacuum induction melting on the recycled material and casts it to obtain recycled material ingots. Recycled materials from different sources and of different types are melted into recycled material ingots with consistent composition. After the chemical composition is tested, they are cut into blocks for later use. This step avoids the fluctuation of melt composition caused by directly adding recycled materials from different sources, in different forms and with different compositions to new materials. The composition is extremely difficult to control, thereby shortening the furnace pre-analysis time, speeding up the smelting rhythm, improving the homogenization of alloy composition and expanding the usable range of recycled materials. In addition, this step can pre-remove the slag, inclusions, impurity elements, etc. carried in the recycled material through vacuum induction melting and casting, thereby reducing the task of removing slag, inclusions and impurity elements caused by mixing and melting recycled materials with new materials.

[0011] (2) Before mixing and melting the recycled material with the new material, the present invention first performs vacuum induction melting on the stable elements and C composition of the new material to fully remove the gaseous impurities such as O and N in the new material before adding the recycled material. This step can avoid the risk of incomplete removal of impurities caused by the weakening of the denitrification ability of the molten pool due to the mixing and melting of the new material and the recycled material (the recycled material contains Ti element, which inhibits the vacuum denitrification reaction). In addition, the present invention performs power-off film formation treatment on the new material molten body when adding the recycled material to the molten and refined new material, which avoids the risk of splashing caused by the addition of material. The present invention found that when adding the recycled material, if the surface of the new material molten body is not protected by film formation (power-off film formation treatment forms a protective film on the surface of the new material molten body), the alloy melt may be eroded by violent splashing, affecting the service life of the crucible furnace lining. At the same time, severe erosion of the furnace lining will cause oxygenation to the alloy melt. Furthermore, without a power-off film-forming process, splashing of the virgin molten material can cause the refractory material in the crucible lining to detach, introducing large inclusions and reducing the purity of the alloy. This invention first performs vacuum induction melting and refining on the virgin material, and then adds recycled material blocks to the virgin molten material during the power-off film-forming stage. This ensures the uniformity of the alloy composition and significantly improves the purity of the final high-temperature alloy ingot, enabling the preparation of large-size, high-purity high-temperature alloy ingots. These ingots can then be used to prepare high-performance large-size bars and large-size ring forgings.

[0012] (3) The present invention employs two vacuum self-consuming remelting processes, and preferably the first process uses a high melting rate, which can effectively remove volatile impurities (such as Pb, Bi, Sn, Sb, As, etc.), reduce the content of impurity gas elements, and fully remove small-sized inclusions. At the same time, the high melting rate can improve production efficiency and reduce production costs. The present invention found that a high melting rate is beneficial to obtaining a full metal molten pool, and small-sized inclusions can fully contact the pasty area on the surface of the crystallizer and be adsorbed and removed. Preferably, the second process uses a low melting rate, which can optimize the solidification structure, reduce segregation and metallurgical defects. The present invention found that a low melting rate produces a shallow and flat molten pool, the molten pool solidifies quickly, the dendrite spacing decreases, the degree of microsegregation is significantly reduced, macrosegregation is improved, the probability of black spots and shrinkage cavities is reduced, and a fine and uniform solidification structure can be obtained. Meanwhile, the low melting rate prolongs the residence time of the alloy melt in the molten pool, providing more time for inclusions to float and be removed, thus avoiding the slag entrapment or electrode shrinkage cavities that can occur with high melting rate smelting. Furthermore, at low melting rates, the formation and dripping of molten droplets at the electrode tip are more stable, reducing droplet splashing and resulting in a smoother remelted ingot surface, thus reducing subsequent peeling losses.

[0013] (4) Compared with the prior art, the proportion of recycled material used in the large-size high-temperature alloy ingots prepared by the present invention can reach more than 40%, the total content of O, N and S impurity elements is less than 30 ppm, the total content of 45 trace elements is less than 200 ppm, and the inclusion number density is less than 30 inclusions / mm 2 The prepared high-temperature alloy ingots are then subjected to high-temperature homogenization diffusion annealing treatment and forged into bars. The mechanical properties of the bars are comparable to those of the virgin material. Attached Figure Description

[0014] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments and comparative examples will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope of the present invention.

[0015] Figure 1 This is a flowchart illustrating the preparation process of high-temperature alloy ingots in some specific embodiments of the present invention; Figure 2 The bar chart shows the impurity element content in the GH4738 high-temperature alloy ingots prepared in Examples 1-6 and Comparative Examples 1-5 of this invention. Figure 3 The bar chart shows the room temperature tensile strength of GH4738 high-temperature alloy bars prepared in Examples 1-6 and Comparative Examples 1-5 of this invention. Detailed Implementation

[0016] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments thereof. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0017] like Figure 1 As shown, the present invention provides a method for preparing a high-temperature alloy ingot in a first aspect, the method comprising the following steps: (1) The returned material is vacuum induction melted and cast to obtain a returned material ingot. The chemical composition of the returned material ingot is detected and it is cut into pieces to obtain returned material pieces. Specifically, for example, the returned material is loaded into a vacuum induction furnace, vacuumed, melted and refined to form a returned material melt body. Then the returned material melt body is cast to obtain a returned material ingot. In this invention, the returned material corresponds to the returned material of the target high-temperature alloy. In this invention, the purpose of detecting the chemical composition of the returned material ingot is to facilitate the calculation of the weight ratio of each element of the subsequent addition of new material. (2) Vacuum induction melting of the new material stable component and C component to obtain a new material melt body, then power off to form a film and add recycled material pieces to the new material melt body for mixing and melting, then adjust the chemical composition by adding the easily oxidized component of the new material and casting to obtain a vacuum induction ingot; specifically, for example, weigh the new material stable component and C component of the target high-temperature alloy and put them into a vacuum induction furnace, evacuate, melt and refine to obtain a new material melt body, then power off to form a film and add the recycled material pieces obtained in step (1) to the new material melt body for mixing and melting, then adjust the chemical composition by adding the easily oxidized component of the new material, after melting and clearing, start the power frequency stirring for 5 minutes, measure the temperature and take samples, fine-tune the composition, after the temperature (meeting the casting temperature of 1420-1440℃) and composition are qualified, fill with argon gas, and tap the steel with power (i.e. casting) to form a vacuum induction ingot containing 40wt% or more of recycled material (also called high-temperature alloy). (Vacuum induction casting ingot); In this invention, preferably, the diameter of the vacuum induction casting ingot is 500~600mm; In this invention, the power-off film formation is achieved by turning off the heating power and cooling the new material melt to form a thin film on the upper surface; In this invention, the mixing and melting is vacuum induction melting. During mixing and melting, all the returned material pieces can be added at once or in batches, and then the heating power can be turned on again to continue vacuum induction melting; The temperature of the mixing and melting is 1500~1550℃, the time of the mixing and melting is 30~60min, and the mixing and melting is carried out under a vacuum pressure of less than or equal to 1Pa; In this invention, the easily oxidizable components of the new material are added according to the standard composition of the target high-temperature alloy; In this invention, it is preferable to add the returned material pieces in batches to avoid a severe temperature drop in the alloy melt caused by adding it all at once, thereby causing local solidification on the surface or inside of the melt, which can effectively reduce energy consumption.

[0018] (3) The electrode ingot is subjected to electroslag remelting, primary vacuum consumable remelting, and secondary vacuum consumable remelting in sequence to obtain a high-temperature alloy ingot; specifically, for example, the vacuum induction ingot obtained in step (2) is trimmed and its surface is polished, and after welding the electrode, it is subjected to electroslag remelting to form an electroslag ingot containing 40wt% or more of recycled material (also referred to as a high-temperature alloy electroslag ingot), and then the electroslag ingot is trimmed and its surface is polished, and after welding the electrode, it is subjected to primary vacuum consumable remelting to form a primary consumable ingot containing 40wt% or more of recycled material (also referred to as a high-temperature alloy primary consumable ingot), and then the primary consumable ingot is forged into a secondary consumable electrode (the purpose of which is to ensure the two self-consumption). (The electrodes are of the same size), then the ends are trimmed and the surface is machined. After welding the electrodes, a second vacuum consumable remelting is performed to form the high-temperature alloy ingot containing 40 wt% or more of recycled material. In this invention, preferably, the diameter of the electroslag ingot is 580 mm to 640 mm, the diameter of the primary consumable ingot is 660 mm to 700 mm, and the diameter of the high-temperature alloy ingot is 660 mm to 700 mm. The high-temperature alloy ingot obtained by this invention contains more than 40% recycled material by mass, the total content of O, N, and S impurity elements in the high-temperature alloy ingot is less than 30 ppm, and the inclusion number density is less than 30 inclusions / mm². 2 .

[0019] There are no existing reports on the use of high proportions of recycled materials to prepare large-size, high-purity ingots. For example, although Chinese patent application CN114369736A discloses a high-temperature alloy and smelting process for increasing the proportion of recycled materials, this patent application involves vacuum induction melting of recycled materials. Typically, the smelting temperature of high-temperature alloys is below 1600℃. However, recycled materials come from numerous sources and have high impurity element content. Relying solely on vacuum induction melting is insufficient to improve the cleanliness and mechanical properties of the high-temperature alloy. Therefore, CN114369736A uses a method of increasing the melting temperature to 1650~1600℃ to remove carbonitride impurities from the alloy. While smelting at 700℃ is possible, ultra-high temperature smelting can easily cause erosion and spalling of the crucible refractory material, introducing large-sized inclusions into the alloy melt. It also increases the oxygen content in the alloy melt, leading to a decrease in the purity of the alloy melt and a significant shortening of the crucible refractory material's service life. Although CN114369736A uses high-temperature smelting to remove carbonitride impurities, it still introduces oxide inclusions. Furthermore, directly mixing and smelting new and recycled materials weakens the nitrogen removal capacity of the molten pool, resulting in incomplete removal of impurity elements. Additionally, adding sufficient Al in the early stages of smelting, which is easily oxidized, can cause severe Al burn-off if added too early.

[0020] Compared with existing technologies, this invention first performs vacuum induction melting on the recycled material and then casts it to obtain recycled material ingots. Recycled materials from different sources, in different forms, and of different types are melted into recycled material ingots with consistent composition. After the chemical composition is qualified, the ingots are sawn into blocks for later use. This step avoids the fluctuations in melt composition caused by directly adding recycled materials from different sources, in different forms, and with different compositions to new materials. The composition is extremely difficult to control, thus shortening the furnace pre-analysis time, accelerating the smelting pace, improving the homogenization of alloy composition, and expanding the usable range of recycled materials. In addition, this step can pre-remove slag, inclusions, and impurity elements carried in the recycled material through a single vacuum induction melting and casting, thereby reducing the task of removing slag, inclusions, and impurity elements caused by mixing and melting recycled materials with new materials.

[0021] Furthermore, compared with the prior art, before mixing and melting the recycled material shards with the new material, the present invention first performs vacuum induction melting on the stable elements and C composition of the new material to fully remove gaseous impurities such as O and N in the new material before adding the recycled material shards. This step can avoid the risk of incomplete removal of impurities caused by the weakening of the denitrification capacity of the molten pool due to the mixing and melting of new and recycled materials (recycled material contains Ti element, which inhibits the vacuum denitrification reaction). In addition, the present invention performs a power-off film formation treatment on the new material molten body when adding the recycled material shards to the molten and refined new material, avoiding the risk of splashing caused by the addition of materials. The present invention found that if the surface of the new material molten body is not protected by a film when adding the recycled material shards (the power-off film formation treatment forms a protective film on the surface of the new material molten body), the alloy melt may be eroded and corroded by violent splashing, affecting the service life of the crucible furnace lining. At the same time, severe lining erosion will cause oxygenation of the alloy melt. Furthermore, without a power-off film-forming process, splashing of the virgin molten material can cause the refractory material in the crucible lining to detach, introducing large inclusions and reducing the purity of the alloy. This invention first performs vacuum induction melting and refining on the virgin material, and then adds recycled material blocks to the virgin molten material during the power-off film-forming stage. This ensures the uniformity of the alloy composition and significantly improves the purity of the final high-temperature alloy ingot, enabling the preparation of large-size, high-purity high-temperature alloy ingots. These ingots can then be used to prepare high-performance large-size bars and large-size ring forgings.

[0022] Existing technologies have not reported any levels of impurity and trace element content in alloys after ingot enlargement. For example, Chinese patent CN117965927A discloses a highly efficient purification smelting method for high-temperature alloy return materials based on hydrogen plasma blowing. Although this patent application utilizes hydrogen plasma to smelt high-temperature alloys containing return materials and can remove impurity elements such as O, N, and S, it requires a plasma torch, which faces problems such as high cost, low stability, and difficult maintenance of the equipment used. Furthermore, the high temperature of the plasma arc during blowing (3000~5000℃) will significantly reduce the service life of the induction furnace crucible. Secondly, hydrogen is a flammable and explosive gas, requiring special storage and usage conditions. Accidents are prone to occur, therefore, the method in CN117965927A is not suitable for industrial-scale large-size vacuum induction furnace high-temperature alloy smelting. Furthermore, current research in this area is mostly limited to laboratory scale and cannot be applied on a large scale for industrial-scale large-size high-temperature alloy smelting containing recycled materials, meaning it cannot produce large-size high-temperature alloy ingots weighing several tons. The high-temperature alloy ingots obtained by CN117965927A only reach a diameter of about 200 mm and weigh only about 100 kg. Moreover, even if attempts were made to apply the method of this patent application to an industrial scale, the significant increase in the target ingot size, coupled with the difficulty in maintaining the stability of hydrogen supply or controlling reaction conditions, could lead to an increase in oxygen, nitrogen, and sulfur content, resulting in a decrease in the purity of the high-temperature alloy. Simultaneously, the limitations of equipment scaling, the need for stable high-purity hydrogen supply, the precise control of ultra-complex reaction systems, stringent safety requirements, and high production costs are all challenges restricting its large-scale industrial application. This invention, however, is suitable for industrial-scale high-temperature alloy smelting containing recycled materials and is applicable to the preparation of high-purity, large-size high-temperature alloy ingots.

[0023] According to some preferred embodiments, the high-temperature alloy ingot contains 40-70% by mass of recycled material (e.g., any value between 40%, 50%, 60%, 70%, or 40-70%); the total amount of 45 trace elements in the high-temperature alloy ingot is less than 200 ppm; and / or the high-temperature alloy ingot is a large-size high-temperature alloy ingot with a diameter of 660 mm to 700 mm (e.g., it can be 660 mm, 670 mm, 680 mm, 690 mm, 700 mm, or any value between 660 mm and 700 mm).

[0024] According to some preferred embodiments, in step (1): before vacuum induction melting of the recycled material, the recycled material is pretreated. The pretreatment involves treating the recycled material at a high temperature of 300~500℃ (e.g., 300℃, 350℃, 400℃, 450℃ or 500℃) in an argon atmosphere for 1~2 hours (e.g., 1 hour, 1.5 hours or 2 hours), cooling it to room temperature, and then soaking it in dilute hydrochloric acid with a concentration of 5~10wt% (e.g., 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%) for 10~30 minutes (e.g., 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes), followed by water washing, ultrasonic treatment and drying. In this invention, drying at 80~100℃ is sufficient, for example. In this invention, the dilute hydrochloric acid uses water as a solvent. The concentration of dilute hydrochloric acid is 5-10 wt%, meaning that the dilute hydrochloric acid contains 5-10% HCl by mass. This invention has found that pretreatment of recycled materials—namely, high-temperature baking and dilute hydrochloric acid soaking—effectively removes oil, dust, cleaning agents, oxides, and impurities from the surface of the recycled materials, reducing their further dissolution and diffusion during vacuum induction melting. This improves the purity of the final alloy ingot. High-temperature baking under an argon atmosphere loosens the oil and oxides on the surface of the recycled materials, and subsequent dilute hydrochloric acid soaking effectively reduces these impurities, effectively removing the surface oxide layer and certain impurities, thus reducing the number of inclusions. This helps reduce the inclusion density in high-temperature alloy ingots and improves the purity of the high-temperature alloy.

[0025] According to some preferred embodiments, in step (2): during the mixed smelting, rare earth metal components are also added, wherein the rare earth metal components are one or more of yttrium (Y), cerium (Ce), lanthanum (La) and neodymium (Nd); preferably at least two of the above rare earth metal components, more preferably a combination of cerium (Ce) and lanthanum (La) or a combination of cerium (Ce) and yttrium (Y), wherein the mass ratio of cerium to lanthanum is preferably (3-5):1, and the mass ratio of cerium to yttrium is preferably (2-5):1; the mass ratio of the rare earth metal components to the recycled material shavings is (0.00015~0.0025):1 (for example, it can be 0.00015:1, 0.00025:1, 0.00035:1, 0.00045:1, 0.00055:1, 0.00065:1, 0.00075:1, 0.0008 ... (0.00095:1, 0.0015:1, 0.0020:1 or 0.0025:1); In this invention, preferably, during the mixed melting process, the recycled material blocks described in this invention are added during the power-off film formation stage for mixed melting, and then new easily oxidizable elements (Al, Ti, B, Zr) and rare earth metal components (Y, Ce, La, Nd) are added to adjust the chemical composition before casting. Among them, the appropriate content of rare earth metal components cerium (Ce), lanthanum (La), and yttrium (Y) can, compared with adding other rare earth metal components or adding rare earth metal components at other stages, reduce the content of impurity elements (such as oxygen, sulfur, etc.) in high-temperature alloy ingots without affecting the current standard composition of high-temperature alloys. If the amount of rare earth metal components added is too high or the timing of addition is inappropriate, they are prone to react with oxygen and sulfur in the alloy melt, significantly reducing the yield of rare earth elements. This invention reveals that the aforementioned rare earth metal components possess strong affinity for both oxygen and sulfur. When cerium is added to the mixed smelting process, it preferentially reacts with impurities such as oxygen and sulfur in the alloy melt to form rare earth oxides (e.g., Ce₂O₃, Y₂O₃, La₂O₃, Nd₂O₃), rare earth oxygen sulfides (e.g., Ce₂O₂S), and rare earth sulfides (e.g., CeS, Y₂S₃, La₂S₃, Nd₂S₃). These rare earth compounds have low solubility in high-temperature alloy melts and are easily aggregated and floated to the surface for removal during the smelting process. By removing large-sized rare earth compounds and effectively reducing the oxygen and sulfur content in the alloy melt, the formation of subsequent fine inclusions is significantly suppressed, effectively reducing the number density of inclusions in the alloy, thereby obtaining high-purity high-temperature alloy ingots. Furthermore, the addition of rare earth metals can promote the formation of a dense protective oxide film on the surface of nickel-based alloys at high temperatures, preventing oxygen from diffusing inward and improving the high-temperature oxidation resistance and corrosion resistance of the alloys; at the same time, it can refine the grains and improve the stability of the alloy structure, thus facilitating the acquisition of high-purity high-temperature alloy ingots with good mechanical properties.

[0026] According to some preferred embodiments, in step (1): the vacuum induction melting is to load the returned material into the vacuum induction furnace, evacuate it, and melt and refine it. The refining temperature is 1500~1600℃ (e.g., 1500℃, 1510℃, 1520℃, 1530℃, 1540℃, 1550℃, 1560℃, 1570℃, 1580℃, 1590℃, 1600℃ or any value between 1500~1600℃); the refining time is not less than 30 minutes, and the evacuation is to evacuate it to a vacuum pressure less than or equal to 1 Pa. In this invention, before smelting, the crucible of the vacuum induction furnace needs to be nickel washed first, so as to avoid the influence of the alloy residue from the previous furnace on the composition of the newly smelted alloy. After the furnace is washed, the vacuum induction furnace is evacuated and the leakage rate is checked. After meeting the requirements, the returned material is loaded into the vacuum induction furnace for melting. This invention performs vacuum induction melting of recycled materials at 1500-1600℃, which avoids the problems of refractory material erosion and flaking, and oxygenation of the alloy melt caused by high-temperature melting in a vacuum induction furnace crucible. Before casting, the recycled material melt formed after vacuum induction melting is passed through two slag-blocking filter channels (also referred to as filter channels). This invention removes large inclusions and slag from the melt by passing it through two slag-blocking filter channels. After passing through the two slag-blocking filter channels, it can be cast into steel ingot molds of any diameter, for example, into ingots with a diameter of 200-300 μm. The steel ingot mold contains m-sized pieces of recycled material. Before the recycled molten material passes through the slag-blocking filter channel, the channel is baked at a temperature ≥1000℃ for 2 hours. This thoroughly removes moisture and volatiles from the refractory lining of the channel, reducing heat loss during casting and preventing the alloy melt from solidifying and forming a crust within the channel, thus minimizing thermal shock damage to the refractory material, extending the service life of the channel lining, preventing cracking and spalling that contaminates the metal, and removing residual contaminants. This ensures the safety and continuity of the casting process and guarantees the final ingot quality. And / or the recycled material pieces weigh 5-10 kg. After chemical composition testing of the recycled ingot, the material is sawn into 5-10 kg pieces, cleaned, and dried for later use.

[0027] According to some preferred embodiments, in step (2): the vacuum induction melting involves loading the stabilizing components of the new material and component C into a vacuum induction furnace, drawing a vacuum, and then melting and refining them. The refining temperature is 1500~1550℃ (for example, it can be any value between 1500℃, 1510℃, 1520℃, 1530℃, 1540℃, 1550℃, or 1500~1550℃), and the refining time is 30~60min (for example, it can be 30min, 40min, etc.). The refining process is stopped after the refining time is 1 minute, 50 minutes, 60 minutes or any value between 30 and 60 minutes, and the difference between two consecutive leakage rates is no higher than 5 mbar·L / s. The vacuuming is performed until the vacuum pressure is less than or equal to 0.5 Pa. Before casting, the mixed melt formed by the mixed melting is passed through two slag-blocking filter channels (also referred to as filter channels) to remove inclusions and slag, and then cast into a steel ingot mold with a diameter of 500 to 600 mm to obtain a vacuum induction ingot.

[0028] According to some preferred embodiments, in step (3): when performing electroslag remelting, the slag system used is a CaO-Al2O3-CaF2-MgO-TiO2 slag system, wherein the CaO-Al2O3-CaF2-MgO-TiO2 slag system contains, by mass percentage, 18~22% (e.g., 18%, 19%, 20%, 21% or 22%) of CaO and 20~24% (e.g., 20%, 21%, 22%) of Al2O3. The slag system comprises 3% or 24% CaF2, 45-55% CaF2 (e.g., 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54% or 55%), MgO, 4-6% MgO (e.g., 4%, 5% or 6%), and TiO2, 2-4% TiO2 (e.g., 2%, 3% or 4%). Preferably, the CaO-Al2O3-CaF2-MgO-TiO2 slag system contains, by mass percentage, 20% CaO, 22% Al2O3, 50% CaF2, 5% MgO, and 3% TiO2. The CaO-Al2O3-CaF2-MgO-TiO2 slag system preferred in this invention effectively improves the purity of the alloy, removes impurities such as oxygen and sulfur, reduces the burn-off loss of easily oxidized elements Al and Ti in the alloy, improves the uniformity of the alloy composition, and helps to obtain higher quality and purer high-temperature alloy ingots.

[0029] According to some preferred embodiments, in electroslag remelting, the amount of slag added, C, is calculated based on the size D of the crystallizer, specifically using the following formula: In the formula, h is the depth of the slag pool, D is the diameter of the crystallizer, h = (1 / 2~1 / 3)×D, and γ is the density of the slag system, which is generally taken as 2400~2500 kg / m³. 3 .

[0030] In this invention, the size of the crystallizer is equal to the size of the ingot. Because metal shrinks during solidification, the actual size of the ingot is slightly smaller than the inner diameter of the crystallizer. Calculations show that the amount of slag used in this invention is 100-180 kg.

[0031] According to some preferred embodiments, after electroslag remelting, the diameter of the obtained electroslag ingot is 580mm to 640mm (for example, it can be any value between 580mm, 590mm, 600mm, 610mm, 620mm, 630mm, 640mm, or 580mm to 640mm). According to some preferred embodiments, after one vacuum arc remelting, the diameter of the obtained primary arc remelting ingot is 660mm to 700mm (for example, it can be any value between 660mm, 670mm, 680mm, 690mm, 700mm, or 660mm to 700mm).

[0032] According to some preferred embodiments, the steady-state melting rate during the electroslag remelting process is 5.0~7.0 kg / min (e.g., it can be any value between 5.0 kg / min, 6.0 kg / min, 7.0 kg / min, or 5.0~7.0 kg / min); the steady-state melting rate during the primary vacuum arc remelting process is 4.5~6.0 kg / min (e.g., it can be any value between 4.5 kg / min, 5.0 kg / min, 5.5 kg / min, 6.0 kg / min, or 4.5~6.0 kg / min); and / or the steady-state melting rate during the secondary vacuum arc remelting process is 3.8~4.5 kg / min (e.g., it can be any value between 3.8 kg / min, 3.9 kg / min, 4.0 kg / min, 4.1 kg / min, 4.2 kg / min, 4.3 kg / min, 4.4 kg / min, 4.5 kg / min, or 3.8~4.5 kg / min).

[0033] In this invention, by precisely controlling the steady-state melting rate of the vacuum arc remelting process, the metallurgical quality, including the depth and shape of the molten pool, dendritic structure and microsegregation, and ingot porosity and shrinkage cavities, can be controlled throughout the smelting process. Preferably, the steady-state melting rates during the primary and secondary vacuum arc remelting processes are controlled to be 4.5~6.0 kg / min and 3.8~4.5 kg / min, respectively. The first-stage vacuum arc remelting uses a high melting rate, which can effectively remove volatile impurities (such as Pb, Bi, Sn, Sb, As, etc.), reduce the content of impurity gas elements, and fully remove small-sized inclusions. At the same time, the high melting rate can improve production efficiency and reduce production costs. This invention finds that a high melting rate is conducive to obtaining a full metal molten pool, and small-sized inclusions can fully contact the pasty area on the surface of the crystallizer, thereby being adsorbed and removed. Preferably, the second-stage vacuum arc remelting uses a low melting rate, which can refine and optimize the solidification structure, reduce segregation and metallurgical defects. This invention finds that a low melting rate produces a shallow and flat molten pool, the molten pool solidifies quickly, the dendrite spacing is reduced, the degree of microsegregation is significantly reduced, macrosegregation is improved, the probability of black spots and shrinkage cavities is reduced, and a fine and uniform solidification structure can be obtained. Meanwhile, the lower melting rate allows for a longer residence time of the alloy melt in the molten pool, providing more time for inclusions to float and be removed. This avoids the slag entrapment or electrode shrinkage cavities that can occur with high melting rates, which can lead to turbulent molten pool formation or electrode shrinkage cavities being drawn into the solidification front. Furthermore, at lower melting rates, the formation and dripping of molten droplets at the electrode tip are more stable, reducing droplet splashing and resulting in a smoother remelted ingot surface, thus reducing subsequent peeling losses.

[0034] According to some preferred embodiments, the high-temperature alloy ingot is a nickel-based high-temperature alloy ingot; the recycled material corresponds to the recycled material of the nickel-based high-temperature alloy, and the recycled material includes block material and / or scrap. The block material includes one or more of the following: casting scrap, induction electrode riser, electroslag, consumable electrode scrap, ingot head and tail scrap, testing scrap, scrap bars, and scrap forging blanks. The scrap includes machining turning material. The stable component of the new material corresponds to the elements in the new material of the nickel-based high-temperature alloy ingot that are not easily oxidized; and / or the easily oxidized component of the new material corresponds to the easily oxidized elements in the new material of the nickel-based high-temperature alloy ingot other than the C component.

[0035] According to some preferred embodiments, the high-temperature alloy ingot is a GH4738 high-temperature alloy ingot, and the stabilizing composition of the new material is nickel (Ni), chromium (Cr), molybdenum (Mo), and cobalt (Co). The easily oxidizable components of the new material are one or more of aluminum (Al), titanium (Ti), boron (B), and zirconium (Zr). In this invention, for example, according to the standard composition requirements of GH4738 high-temperature alloy ingots, stabilizing components, C components, and easily oxidizable components of the new material are added. In this invention, the standard composition of the GH4738 high-temperature alloy ingot includes, by mass percentage: C 0.02~0.10%; Cr 18~21%; Co 12~15%; Mo 3.5~5%; Ti 2.75~3.25%; Al 1.2~1.6%; Zr 0.02~0.07%; B 0.003~0.010%; Ni balance.

[0036] In a second aspect, the present invention provides a high-temperature alloy ingot prepared by the preparation method described in the first aspect.

[0037] In a third aspect, this invention provides the application of a high-temperature alloy ingot prepared by the method described in the first aspect in the preparation of bars or ring forgings. In this invention, the high-temperature alloy ingot can be used to prepare large-size bars and large-size ring forgings. In this invention, for example, the obtained high-temperature alloy ingot is subjected to high-temperature homogenization diffusion annealing treatment, followed by forging to obtain the bar, the mechanical properties of which are comparable to those of a new material. In this invention, a two-stage high-temperature homogenization diffusion annealing treatment is used, for example, first performing a first-stage homogenization treatment at 1160~1180℃ for 20~30h, then performing a second-stage homogenization treatment at 1190~1200℃ for 25~72h, and finally cooling in the furnace to 550~600℃ before air cooling. In this invention, the forging heating temperature is 1150~1170℃, and the final forging temperature should not be lower than 1050℃.

[0038] The embodiments of the present invention will be described in detail below with reference to specific examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the present invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0039] Example 1 Taking GH4738 high-temperature alloy as an example, high-purity large-size GH4738 high-temperature alloy ingots with a return material ratio of 40wt% (containing 40% of the mass of return material) are prepared.

[0040] ① Add GH4738 high-temperature alloy recycled materials of different sources and types into a vacuum induction furnace, evacuate and melt and refine them. The refining temperature is 1550℃, the vacuum pressure is 0.3Pa, and the refining time is 30min to form a recycled material melt. Then, the recycled material melt is passed through two slag-blocking filter channels to remove floating slag, and then cast into a steel ingot mold with a diameter of 220mm to obtain a recycled material ingot. The chemical composition of the recycled material ingot is sampled and tested. Then, it is sawn into blocks to obtain recycled material blocks. The recycled material blocks are then cleaned and dried for later use.

[0041] ② According to the standard composition requirements of GH4738 high-temperature alloy, weigh out the stabilizing components Ni, Cr, Mo, Co, and C of the new material according to the required elements of GH4738 high-temperature alloy, and put them into a vacuum induction furnace for vacuuming and melting and refining. The refining temperature is 1520℃, the vacuum pressure is 0.3Pa, the refining time is 50min, and the difference in leakage rate between two adjacent refining operations is 2.8mbar·L / s. Then stop the refining to obtain the new material melt. Then turn off the power to form a film. Specifically, turn off the heating power and wait for the new material melt in the crucible to cool until a thin film appears on the upper surface. Then add the recycled material blocks obtained in step ① in two batches for mixing and melting. The refining process involves mixing and melting at a temperature of 1500℃ and a vacuum pressure of 0.3Pa. After the recycled material is cut into blocks and melted, refining continues for 20 minutes. Samples are taken to test the chemical composition of the alloy. The chemical composition of the high-temperature alloy is adjusted by adding easily oxidizable components Al, Ti, B, and Zr from the new material to meet the standard composition requirements of GH4738 high-temperature alloy. After melting, the alloy melt is stirred at industrial frequency for 5 minutes to ensure uniform mixing and obtain a mixed melt. The mixed melt is then passed through two slag-blocking filter channels to remove slag, and then cast into a steel ingot mold with a diameter of 500mm to obtain a vacuum induction ingot with a recycled material ratio of 40wt%.

[0042] ③ The vacuum induction casting ingot containing 40wt% recycled material obtained in step ② is trimmed at both ends and machined. After welding electrodes, it is electroslag remelted to form an electroslag casting ingot containing 40wt% recycled material. The diameter of the electroslag casting ingot is 580mm. When performing electroslag remelting, the slag system used is CaO-Al2O3-CaF2-MgO-TiO2 slag system, which contains CaO 20%, Al2O3 22%, CaF2 50%, MgO 5% and TiO2 3% by mass percentage. The amount of slag (the amount of slag system used) is 130kg. The steady-state melting rate during the electroslag remelting process is 5.8kg / min.

[0043] ④ The electroslag ingot containing 40wt% recycled material obtained in step ③ is cut off at the head and tail and its surface is machined. After welding the electrodes, it is subjected to a vacuum self-consumable remelting to form a primary self-consumable ingot containing 40wt% recycled material. The diameter of the primary self-consumable ingot is 660mm. The steady-state melting rate during the primary vacuum self-consumable remelting process is 4.8kg / min.

[0044] ⑤ The primary consumable ingot containing 40wt% recycled material obtained in step ④ is forged at 1150℃ into a secondary consumable electrode with a diameter of 580mm. Then, the head and tail are cut off and the surface is machined. After welding the electrode, a secondary vacuum consumable remelting is performed to form a GH4738 high-temperature alloy ingot containing 40wt% recycled material (i.e., a high-purity large-size GH4738 high-temperature alloy ingot). The diameter of the obtained high-temperature alloy ingot is 660mm. The steady-state melting rate during the secondary vacuum consumable remelting process is 4.0kg / min.

[0045] Experimental Results: Following the methods described in HB 5220.49-2008 and HB 5220.6-2008, the GH4738 high-temperature alloy ingot prepared in this embodiment, containing 40wt% recycled material, had a diameter of 660mm, an O content of 7ppm, a N content of 11ppm, a S content of 5ppm, and trace elements of less than 200ppm for 45 elements. The inclusion number density was 22.97 inclusions / mm². 2 In this embodiment, a GH4738 high-temperature alloy ingot with a diameter of 660 mm and containing 40 wt% recycled material was subjected to high-temperature homogenization treatment (first homogenization treatment at 1160℃ for 24 hours, then homogenization treatment at 1190℃ for 72 hours, and finally furnace cooling to 600℃), and then air-cooled. It was forged into bars at 1150℃, and its mechanical properties were tested according to the methods in GB / T 228.1-2021 and GB / T 2039-2024. The measured room temperature tensile strength was 1263 MPa, elongation was 19.8%, the 760℃ tensile strength was 873 MPa, elongation was 29%, and the creep rupture time at 730℃ / 550 MPa was ≥25 hours (e.g., Figures 2 to 3 (As shown).

[0046] Example 2 Taking GH4738 high-temperature alloy as an example, high-purity large-size GH4738 high-temperature alloy ingots with a return material ratio of 70wt% (containing 70% of the mass of return material) are prepared.

[0047] ① Add GH4738 high-temperature alloy recycled materials of different sources and types into a vacuum induction furnace, evacuate and melt and refine them. The refining temperature is 1580℃, the vacuum pressure is 0.5Pa, and the refining time is 50min to form a recycled material melt. Then, the recycled material melt is passed through two slag-blocking filter channels to remove floating slag, and then cast into a steel ingot mold with a diameter of 220mm to obtain a recycled material ingot. The chemical composition of the recycled material ingot is sampled and tested. Then, it is sawn into blocks to obtain recycled material blocks. The recycled material blocks are then cleaned and dried for later use.

[0048] ② According to the standard composition requirements of GH4738 high-temperature alloy, weigh the new material containing the stabilizing components Ni, Cr, Mo, Co, and C as required by GH4738 high-temperature alloy, and put it into a vacuum induction furnace for vacuuming and melting and refining. The refining temperature is 1500℃, the vacuum pressure is 0.4Pa, the refining time is 40min, and the difference between two adjacent leakage rates is 2.2mbar·L / s, at which point the refining is stopped. Then, the power was turned off to form a film. Specifically, the heating power was turned off, and the new material melt in the crucible was allowed to cool until a thin film appeared on the upper surface. Then, the recycled material blocks obtained in step ① were added in three batches for mixing and melting. The mixing and melting temperature (refining temperature) was 1500℃, and the vacuum pressure was 0.3Pa. After the recycled material blocks were melted clean, the refining continued for 20 minutes. The chemical composition of the alloy was sampled and tested. The chemical composition of the high-temperature alloy was adjusted by adding easily oxidizable components Al, Ti, B and Zr from the new material to meet the standard composition requirements of GH4738 high-temperature alloy, and a mixed melt was obtained. The mixed melt was then passed through two slag-blocking filter channels to remove slag, and then cast into a steel ingot mold with a diameter of 550mm to obtain a vacuum induction ingot with a recycled material ratio of 70wt%.

[0049] ③ The vacuum induction casting ingot containing 70wt% recycled material obtained in step ② is trimmed at both ends and machined. After welding electrodes, it is electroslag remelted to form an electroslag casting ingot containing 70wt% recycled material. The diameter of the electroslag casting ingot is 620mm. When performing electroslag remelting, the slag system used is CaO-Al2O3-CaF2-MgO-TiO2 slag system, which contains CaO 20%, Al2O3 22%, CaF2 50%, MgO 5% and TiO2 3% by mass percentage. The amount of slag (the amount of slag system used) is 160kg. The steady-state melting rate during the electroslag remelting process is 6.2kg / min.

[0050] ④ The electroslag ingot containing 70wt% recycled material obtained in step ③ is trimmed at the head and tail and its surface is machined. After welding the electrodes, it is subjected to a vacuum consumable remelting process to form a primary consumable ingot containing 70wt% recycled material. The diameter of the primary consumable ingot is 700mm. The steady-state melting rate during the primary vacuum consumable remelting process is 5.2kg / min.

[0051] ⑤ The primary consumable ingot containing 70wt% recycled material obtained in step ④ is forged at 1150℃ into a secondary consumable electrode with a diameter of 620mm. Then, the head and tail are cut off and the surface is machined. After welding the electrode, a secondary vacuum consumable remelting is performed to form a GH4738 high-temperature alloy ingot containing 70wt% recycled material (i.e., a high-purity large-size GH4738 high-temperature alloy ingot). The diameter of the obtained GH4738 high-temperature alloy ingot is 700mm. The steady-state melting rate during the secondary vacuum consumable remelting process is 4.2kg / min.

[0052] Experimental Results: Following the methods described in HB 5220.49-2008 and HB 5220.6-2008, the GH4738 high-temperature alloy ingot prepared in this embodiment, containing 70 wt% recycled material, had a diameter of 700 mm, an O content of 9 ppm, a N content of 14 ppm, a S content of 5 ppm, and trace elements of 45 elements were less than 200 ppm. The inclusion number density was 28.62 inclusions / mm². 2 In this embodiment, a 700mm diameter GH4738 high-temperature alloy ingot containing 70wt% recycled material underwent high-temperature homogenization diffusion annealing (first homogenization at 1180℃ for 24 hours, then homogenization at 1200℃ for 76 hours, and finally furnace cooling to 600℃), followed by air cooling. It was then forged into bars at 1150℃, and its mechanical properties were tested according to the methods in GB / T 228.1-2021 and GB / T 2039-2024. The measured room temperature tensile strength was 1285MPa, elongation 17.5%; the 760℃ tensile strength was 861MPa, elongation 25.6%; and the 730℃ / 550MPa creep rupture time was ≥25 hours (e.g., ...). Figures 2 to 3 (As shown).

[0053] Example 3 Taking GH4738 high-temperature alloy as an example, high-purity large-size GH4738 high-temperature alloy ingots with a return material ratio of 70wt% (containing 70% of the mass of return material) are prepared.

[0054] ① Add GH4738 high-temperature alloy recycled materials of different sources and types into a vacuum induction furnace, evacuate and melt and refine them. The refining temperature is 1550℃, the vacuum pressure is 0.5Pa, and the refining time is 60min to form a recycled material melt. Then, the recycled material melt is passed through two slag-blocking filter channels to remove floating slag, and then cast into a steel ingot mold with a diameter of 220mm to obtain a recycled material ingot. The chemical composition of the recycled material ingot is sampled and tested. Then, it is sawn into blocks to obtain recycled material blocks. The recycled material blocks are then cleaned and dried for later use.

[0055] ② According to the standard composition requirements of GH4738 high-temperature alloy, weigh the new material containing the stabilizing components Ni, Cr, Mo, Co, and C as required by GH4738 high-temperature alloy, and put it into a vacuum induction furnace for vacuuming and melting and refining. The refining temperature is 1500℃, the vacuum pressure is 0.2Pa, the refining time is 30min, and the difference between two consecutive leakage rates is 2.2mbar·L / s, at which point the refining is stopped. Then, the power was turned off to form a film. Specifically, the heating power was turned off, and the new material melt in the crucible was allowed to cool until a thin film appeared on the upper surface. Then, the recycled material blocks obtained in step ① were added in three batches for mixing and melting. The mixing and melting temperature (refining temperature) was 1500℃, and the vacuum pressure was 0.1Pa. After the recycled material blocks were melted clean, the refining continued for 20 minutes. The chemical composition of the alloy was sampled and tested. The chemical composition of the high-temperature alloy was adjusted by adding easily oxidized components Al, Ti, B and Zr from the new material to meet the standard composition requirements of GH4738 high-temperature alloy, and a mixed melt was obtained. The mixed melt was then passed through two slag-blocking filter channels to remove slag, and then cast into a steel ingot mold with a diameter of 550mm to obtain a vacuum induction ingot with a recycled material ratio of 70wt%.

[0056] ③ The vacuum induction casting ingot containing 70wt% recycled material obtained in step ② is trimmed at both ends and machined. After welding electrodes, it is electroslag remelted to form an electroslag casting ingot containing 70wt% recycled material. The diameter of the electroslag casting ingot is 610mm. When performing electroslag remelting, the slag system used is CaO-Al2O3-CaF2-MgO-TiO2 slag system, which contains CaO 20%, Al2O3 22%, CaF2 50%, MgO 5% and TiO2 3% by mass percentage. The amount of slag (the amount of slag system used) is 150kg. The steady-state melting rate during the electroslag remelting process is 6.0kg / min.

[0057] ④ The electroslag ingot containing 70wt% recycled material obtained in step ③ is cut off at the head and tail and its surface is machined. After welding the electrodes, it is subjected to a vacuum self-consumable remelting to form a primary self-consumable ingot containing 70wt% recycled material. The diameter of the primary self-consumable ingot is 700mm. The steady-state melting rate during the primary vacuum self-consumable remelting process is 5.0kg / min.

[0058] ⑤ The primary consumable ingot containing 70wt% recycled material obtained in step ④ is forged at 1150℃ into a secondary consumable electrode with a diameter of 610mm. Then, the head and tail are cut off and the surface is machined. After welding the electrode, a secondary vacuum consumable remelting is performed to form a GH4738 high-temperature alloy ingot containing 70wt% recycled material (i.e., a high-purity large-size GH4738 high-temperature alloy ingot). The diameter of the obtained GH4738 high-temperature alloy ingot is 700mm. The steady-state melting rate during the secondary vacuum consumable remelting process is 4.0kg / min.

[0059] Experimental Results: Following the methods described in HB 5220.49-2008 and HB 5220.6-2008, the GH4738 high-temperature alloy ingot prepared in this embodiment, containing 70 wt% recycled material, had a diameter of 700 mm, an O content of 8 ppm, a N content of 13 ppm, a S content of 6 ppm, and trace elements of 45 elements were less than 200 ppm. The inclusion number density was 28.07 inclusions / mm². 2 In this embodiment, a 700mm diameter GH4738 high-temperature alloy ingot containing 70wt% recycled material underwent high-temperature homogenization diffusion annealing (first homogenization treatment at 1160℃ for 24 hours, then a second homogenization treatment at 1190℃ for 65 hours, and finally furnace cooling to 600℃), followed by air cooling. It was then forged into bars at 1150℃, and its mechanical properties were tested according to the methods in GB / T 228.1-2021 and GB / T 2039-2024. The measured room temperature tensile strength was 1289MPa, elongation was 19.4%, 760℃ tensile strength was 850MPa, elongation was 23.3%, and 730℃ / 550MPa creep rupture time was ≥25 hours (e.g., Figures 2 to 3 (As shown).

[0060] Example 4 Taking GH4738 high-temperature alloy as an example, high-purity large-size GH4738 high-temperature alloy ingots with a return material ratio of 70wt% (containing 70% of the mass of return material) are prepared.

[0061] ① The GH4738 high-temperature alloy recycled materials from different sources and of different types were pretreated. The pretreatment involved treating the GH4738 high-temperature alloy recycled materials at 400℃ in an argon atmosphere for 2 hours, cooling them to room temperature, soaking them in 5wt% dilute hydrochloric acid for 20 minutes, then washing them with water, ultrasonic treatment, and drying them. Then, they were placed in a vacuum induction furnace, vacuumed, and melted and refined. The refining temperature was 1580℃, the vacuum pressure was 0.5Pa, and the refining time was 50 minutes to form a recycled material melt. The recycled material melt was then passed through two slag-blocking filter channels to remove slag, and then cast into a steel ingot mold with a diameter of 220mm to obtain a recycled material ingot. The chemical composition of the recycled material ingot was sampled and tested. Then, it was sawn into blocks to obtain recycled material blocks. The recycled material blocks were then cleaned and dried for later use.

[0062] ② is the same as step ② in Example 2.

[0063] ③ is the same as step ③ in Example 2.

[0064] ④ is the same as step ④ in Example 2.

[0065] ⑤ is the same as step ⑤ in Example 2.

[0066] Experimental Results: Following the methods described in HB 5220.49-2008 and HB 5220.6-2008, the GH4738 high-temperature alloy ingot prepared in this embodiment, containing 70 wt% recycled material, had a diameter of 700 mm, an O content of 6 ppm, a N content of 13 ppm, a S content of 4 ppm, and trace elements of less than 200 ppm. The inclusion number density was 21.14 inclusions / mm². 2 In this embodiment, a 700mm diameter GH4738 high-temperature alloy ingot containing 70wt% recycled material underwent high-temperature homogenization diffusion annealing (first homogenization at 1180℃ for 24 hours, then a second homogenization at 1200℃ for 76 hours, and finally furnace cooling to 600℃), followed by air cooling. It was then forged into bars at 1150℃, and its mechanical properties were tested according to the methods in GB / T 228.1-2021 and GB / T 2039-2024. The measured room temperature tensile strength was 1292MPa, elongation was 18.3%, 760℃ tensile strength was 867MPa, elongation was 26.7%, and 730℃ / 550MPa creep rupture time was ≥25 hours (e.g., Figures 2 to 3 (As shown).

[0067] Example 5 Taking GH4738 high-temperature alloy as an example, high-purity large-size GH4738 high-temperature alloy ingots with a return material ratio of 70wt% (containing 70% of the mass of return material) are prepared.

[0068] ① The GH4738 high-temperature alloy recycled materials from different sources and of different types were pretreated. The pretreatment involved treating the GH4738 high-temperature alloy recycled materials at 400℃ in an argon atmosphere for 2 hours, cooling them to room temperature, soaking them in 5wt% dilute hydrochloric acid for 20 minutes, then washing them with water, ultrasonic treatment, and drying them. Then, they were placed in a vacuum induction furnace, vacuumed, and melted and refined. The refining temperature was 1580℃, the vacuum pressure was 0.5Pa, and the refining time was 50 minutes to form a recycled material melt. The recycled material melt was then passed through two filtration channels to remove slag and cast into a steel ingot mold with a diameter of 220mm to obtain a recycled material ingot. The chemical composition of the recycled material ingot was sampled and tested. Then, it was sawn into blocks to obtain recycled material cut blocks. The recycled material cut blocks were then cleaned and dried for later use.

[0069] ② According to the standard composition requirements of GH4738 high-temperature alloy, weigh the new material containing the stabilizing components Ni, Cr, Mo, Co, and C as required by GH4738 high-temperature alloy, and put it into a vacuum induction furnace for vacuuming and melting and refining. The refining temperature is 1500℃, the vacuum pressure is 0.4Pa, the refining time is 40min, and the difference between two adjacent leakage rates is 2.2mbar·L / s, at which point the refining is stopped. Then, the power was turned off to form a film. Specifically, the heating power was turned off, and the new material melt in the crucible was allowed to cool until a thin film appeared on the upper surface. Then, the recycled material blocks obtained in step ① were added in three batches for mixing and melting. The mixing and melting temperature (refining temperature) was 1500℃, and the vacuum pressure was 0.3Pa. After the recycled material blocks were melted clean, the refining continued for 20 minutes. The chemical composition of the alloy was sampled and tested. The chemical composition of the high-temperature alloy was adjusted by adding easily oxidizable components Al, Ti, B, Zr from the new material, and rare earth metal components Ce and La (mass ratio of 3:1) to meet the standard composition requirements of GH4738 high-temperature alloy, thus obtaining a mixed melt. The mixed melt was then passed through two slag-blocking filter channels to remove slag, and then cast into a steel ingot mold with a diameter of 550mm to obtain an electrode ingot with a recycled material ratio of 70wt%. The mass ratio of the rare earth metal components to the recycled material blocks was 0.0003:1.

[0070] ③ is the same as step ③ in Example 2.

[0071] ④ is the same as step ④ in Example 2.

[0072] ⑤ is the same as step ⑤ in Example 2.

[0073] Experimental Results: Following the methods described in HB 5220.49-2008 and HB 5220.6-2008, the GH4738 high-temperature alloy ingot prepared in this embodiment, containing 70 wt% recycled material, had a diameter of 700 mm, an O content of 5 ppm, a N content of 11 ppm, a S content of 3 ppm, and trace elements of 45 elements were less than 200 ppm. The inclusion number density was 18.8 inclusions / mm². 2 In this embodiment, a 700mm diameter GH4738 high-temperature alloy ingot containing 70wt% recycled material underwent high-temperature homogenization diffusion annealing (first homogenization at 1180℃ for 24 hours, then homogenization at 1200℃ for 76 hours, and finally cooled to 600℃). It was then forged into bars at 1150℃, and its mechanical properties were tested according to the methods in GB / T 228.1-2021 and GB / T 2039-2024. The measured room temperature tensile strength was 1311MPa, elongation was 19.6%, the 760℃ tensile strength was 875MPa, elongation was 29.1%, and the 730℃ / 550MPa creep rupture time was ≥25 hours (e.g., ...). Figures 2 to 3 (As shown).

[0074] Example 6 Example 6 is basically the same as Example 5, except that: ② According to the standard composition requirements of GH4738 high-temperature alloy, weigh the new material containing the stabilizing components Ni, Cr, Mo, Co, and C as required by GH4738 high-temperature alloy, and put it into a vacuum induction furnace for vacuuming and melting and refining. The refining temperature is 1500℃, the vacuum pressure is 0.4Pa, the refining time is 40min, and the difference between two adjacent leakage rates is 2.2mbar·L / s, at which point the refining is stopped. Then, the power was turned off to form a film. Specifically, the heating power was turned off, and the virgin material melt in the crucible was allowed to cool until a thin film appeared on the upper surface. The rare earth metal component yttrium (Y) was added, and then the recycled material blocks obtained in step ① were added in three batches for mixing and melting. The mixing and melting temperature (refining temperature) was 1500℃, and the vacuum pressure was 0.3Pa. After the recycled material blocks were melted clean, the refining continued for 20 minutes. Then, the chemical composition of the high-temperature alloy was adjusted by adding easily oxidizable components Al, Ti, B, and Zr from the virgin material to meet the standard composition requirements of GH4738 high-temperature alloy, thus obtaining a mixed melt. Subsequently, the mixed melt was filtered twice to remove slag, and then cast into a steel ingot mold with a diameter of 550mm to obtain a vacuum induction ingot with a recycled material ratio of 70wt%. The mass ratio of the rare earth metal component yttrium to the recycled material blocks was 0.0003:1.

[0075] Experimental Results: Following the methods described in HB 5220.49-2008 and HB 5220.6-2008, the GH4738 high-temperature alloy ingot prepared in this embodiment, containing 70 wt% recycled material, had a diameter of 700 mm, an O content of 7 ppm, a N content of 14 ppm, a S content of 4 ppm, and trace elements of 45 elements were less than 200 ppm. The inclusion number density was 23.73 inclusions / mm². 2 In this embodiment, a 700mm diameter GH4738 high-temperature alloy ingot containing 70wt% recycled material underwent high-temperature homogenization diffusion annealing (first homogenization at 1180℃ for 24 hours, then homogenization at 1200℃ for 76 hours, and finally cooled to 600℃). It was then forged into bars at 1150℃, and its mechanical properties were tested according to the methods in GB / T 228.1-2021 and GB / T 2039-2024. The measured room temperature tensile strength was 1294MPa, elongation was 18.1%, the 760℃ tensile strength was 863MPa, elongation was 26.2%, and the 730℃ / 550MPa creep rupture time was ≥25 hours (e.g., ...). Figures 2 to 3 (As shown).

[0076] Comparative Example 1 Taking GH4738 high-temperature alloy as an example, it is smelted using brand-new materials.

[0077] ① According to the standard composition requirements of GH4738 high-temperature alloy, the stabilizing components Ni, Cr, Mo, Co, and C of the new material were weighed according to the elements required for GH4738 high-temperature alloy and loaded into a vacuum induction furnace for vacuuming and melting and refining. The refining temperature was 1520℃, the vacuum pressure was evacuated to 0.3Pa, the refining time was 50min, and the difference in leakage rate between two adjacent times was 2.8mbar·L / s. The refining was then stopped, and the power was turned off to form a film. The chemical composition of the high-temperature alloy was adjusted by adding the easily oxidized components Al, Ti, B, and Zr of the new material to meet the standard composition requirements of GH4738 high-temperature alloy, thus obtaining the new material melt. The new material melt was then passed through two slag-blocking filter channels to remove slag, and then cast into a steel ingot mold with a diameter of 500mm to obtain a vacuum induction casting ingot.

[0078] ② The vacuum induction casting obtained in step ① is trimmed at both ends and machined, and then electrodes are welded on before electroslag remelting to form an electroslag casting with a diameter of 580 mm. During electroslag remelting, the slag system used is CaO-Al2O3-CaF2-MgO-TiO2, which contains CaO 20%, Al2O3 22%, CaF2 50%, MgO 5%, and TiO2 3% by mass percentage. The amount of slag (the amount of slag system used) is 130 kg. The steady-state melting rate during the electroslag remelting process is 5.8 kg / min.

[0079] ③ The electroslag ingot obtained in step ② is cut off at the head and tail and its surface is machined. After welding the electrode, it is vacuum consumable remelted to form a high-temperature alloy consumable ingot with a diameter of 660 mm. The steady-state melting rate during the vacuum consumable remelting process is 4.8 kg / min.

[0080] Experimental Results: Following the methods described in HB 5220.49-2008 and HB 5220.6-2008, the virgin GH4738 high-temperature alloy ingot prepared in this comparative example had a diameter of 660 mm, an O content of 6 ppm, a N content of 9 ppm, a S content of 3 ppm, and trace elements of 45 elements were less than 200 ppm. The inclusion number density was 17.56 inclusions / mm². 2 The GH4738 high-temperature alloy ingots with a diameter of 660mm used in this comparative example underwent high-temperature homogenization diffusion annealing (first homogenization at 1160℃ for 24 hours, then homogenization at 1190℃ for 72 hours, and finally furnace cooling to 600℃), followed by air cooling. They were forged into bars at 1150℃ and their mechanical properties were tested according to the methods in GB / T 228.1-2021 and GB / T 2039-2024. The measured room temperature tensile strength was 1277MPa, elongation was 19.9%, the 760℃ tensile strength was 879MPa, elongation was 29.3%, and the 730℃ / 550MPa creep rupture time was ≥25 hours (e.g., ...). Figures 2 to 3 (As shown).

[0081] Comparative Example 2 Taking GH4738 high-temperature alloy as an example, GH4738 high-temperature alloy ingots with a return material ratio of 70wt% (containing 70% of the mass of return material) are prepared.

[0082] ① According to the standard composition requirements of GH4738 high-temperature alloy, recycled GH4738 high-temperature alloy materials from different sources and of different types, as well as new materials weighing out the stabilizing components Ni, Cr, Mo, Co, and C according to the required elements for GH4738 high-temperature alloy, were added to a vacuum induction furnace for vacuuming and melting and refining. The refining temperature was 1580℃, the vacuum pressure was reduced to 0.5Pa, and the refining time was 50min. The refining was stopped when the difference in leakage rate between two consecutive refining operations was 2.2mbar·L / s. Then, the power was turned off, and the film was formed. The easily oxidizable components Al and Ti were then added to the new materials. B and Zr are used to adjust the chemical composition of the high-temperature alloy so that the alloy composition meets the standard composition requirements of GH4738 high-temperature alloy, resulting in a mixed melt. The mixed melt is then passed through two filtration channels to remove slag and inclusions, and then cast into a steel ingot mold with a diameter of 500 mm to obtain a vacuum induction ingot containing 70 wt% recycled material. In the vacuum induction ingot, the mass percentage of recycled GH4738 high-temperature alloy from different sources and types is 70%, and the sum of the mass percentages of the stabilizing components, C components, and easily oxidized components of the virgin material is 30%.

[0083] ② The vacuum induction casting ingot containing 70wt% recycled material obtained in step ① is trimmed at both ends and machined. After welding electrodes, it is electroslag remelted to form an electroslag casting ingot containing 70wt% recycled material. The diameter of the electroslag casting ingot is 620mm. When performing electroslag remelting, the slag system used is CaO-Al2O3-CaF2-MgO-TiO2 slag system, which contains CaO 20%, Al2O3 22%, CaF2 50%, MgO 5% and TiO2 3% by mass percentage. The amount of slag (the amount of slag system used) is 160kg. The steady-state melting rate during the electroslag remelting process is 6.2kg / min.

[0084] ③ The electroslag ingot containing 70wt% recycled material obtained in step ② is cut off at the head and tail and its surface is machined. After welding the electrodes, it is subjected to a vacuum self-consumable remelting to form a primary self-consumable ingot containing 70wt% recycled material. The diameter of the primary self-consumable ingot is 700mm. The steady-state melting rate during the primary vacuum self-consumable remelting process is 5.2kg / min.

[0085] ④ The primary consumable ingot containing 70wt% recycled material obtained in step ③ is forged at 1150℃ into a secondary consumable electrode with a diameter of 620mm. Then, the head and tail are cut off and the surface is machined. After welding the electrode, a secondary vacuum consumable remelting is performed to form a GH4738 high-temperature alloy ingot containing 70wt% recycled material (i.e., a high-purity large-size GH4738 high-temperature alloy ingot). The diameter of the obtained GH4738 high-temperature alloy ingot is 700mm. The steady-state melting rate during the secondary vacuum consumable remelting process is 4.2kg / min.

[0086] Experimental Results: Following the methods described in HB 5220.49-2008 and HB 5220.6-2008, the GH4738 high-temperature alloy ingot prepared in this comparative example, containing 70 wt% recycled material, had a diameter of 700 mm, an O content of 13 ppm, a N content of 23 ppm, a S content of 8 ppm, and trace elements of 45 elements were less than 200 ppm. The inclusion number density was 116.35 inclusions / mm². 2 The GH4738 high-temperature alloy ingot with a diameter of 700 mm and containing 70 wt% recycled material was subjected to high-temperature homogenization diffusion annealing (first homogenization at 1180℃ for 24 h, then homogenization at 1200℃ for 76 h, and finally furnace cooling to 600℃), and then air-cooled. It was forged into bars at 1150℃, and its mechanical properties were tested according to the methods in GB / T 228.1-2021 and GB / T 2039-2024. The measured room temperature tensile strength was 1164 MPa, elongation was 14.2%, the 760℃ tensile strength was 786 MPa, elongation was 21.2%, and the 730℃ / 550 MPa creep rupture time was 17 hours (e.g., ...). Figures 2 to 3 (As shown).

[0087] Comparative Example 3 Taking GH4738 high-temperature alloy as an example, GH4738 high-temperature alloy ingots with a return material ratio of 70wt% (containing 70% of the mass of return material) are prepared.

[0088] ①The steps are the same as in Example 2.

[0089] ② is the same as step ② in Example 2.

[0090] ③ is the same as step ③ in Example 2.

[0091] ④ The electroslag ingot containing 70wt% recycled material obtained in step ③ is cut off at the head and tail and its surface is machined. After welding the electrodes, it is vacuum consumable remelted to form a consumable ingot containing 70wt% recycled material. The diameter of the consumable ingot is 700mm, which is the GH4738 high temperature alloy ingot.

[0092] Experimental Results: Following the methods described in HB 5220.49-2008 and HB 5220.6-2008, the GH4738 high-temperature alloy ingot prepared in this comparative example, containing 70 wt% recycled material, had a diameter of 700 mm, an O content of 12 ppm, a N content of 21 ppm, a S content of 7 ppm, and trace elements of 45 elements were less than 200 ppm. The inclusion number density was 95.88 inclusions / mm². 2The GH4738 high-temperature alloy ingot with a diameter of 700 mm and containing 70 wt% recycled material in this comparative example underwent high-temperature homogenization diffusion annealing treatment (first homogenization treatment at 1180℃ for 24 h, then second homogenization treatment at 1200℃ for 76 h, and finally furnace cooling to 600℃), and was then air-cooled after being removed from the furnace. It was forged into bars at 1150℃, and mechanical properties were tested according to the methods in GB / T 228.1-2021 and GB / T 2039-2024. The measured room temperature tensile strength was 1198 MPa, elongation was 14.8%, 760℃ tensile strength was 809 MPa, elongation was 21.7%, and 730℃ / 550 MPa creep rupture time was 19 hours (e.g., ...). Figures 2 to 3 (As shown).

[0093] Comparative Example 4 Comparative Example 4 is basically the same as Example 2, except that: ② According to the standard composition requirements of GH4738 high-temperature alloy, the stabilizing components Ni, Cr, Mo, and Co, as well as the C component, of the new material and the recycled material obtained in step ① were weighed and placed into a vacuum induction furnace for vacuuming and melting and refining. The refining temperature was 1500℃, the vacuum pressure was evacuated to 0.4Pa, the refining time was 60min, and the difference in leakage rate between two adjacent refining operations was 2.2 mbar·L / s. The refining was then stopped. After power was cut off and film was formed, the chemical composition of the high-temperature alloy was adjusted by adding easily oxidizable components Al, Ti, B, and Zr from the new material to meet the standard composition requirements of GH4738 high-temperature alloy, resulting in a mixed melt. The mixed melt was then passed through two filtration channels to remove slag, and then cast into a steel ingot mold with a diameter of 550mm to obtain a vacuum induction ingot with a recycled material ratio of 60wt%.

[0094] Experimental Results: Following the methods described in HB 5220.49-2008 and HB 5220.6-2008, the GH4738 high-temperature alloy ingot prepared in this comparative example, containing 70 wt% recycled material, had a diameter of 700 mm, an O content of 11 ppm, a N content of 18 ppm, a S content of 7 ppm, and trace elements of 45 elements were less than 200 ppm. The inclusion number density was 71.31 inclusions / mm². 2The GH4738 high-temperature alloy ingot with a diameter of 700 mm and containing 70 wt% recycled material in this comparative example underwent high-temperature homogenization diffusion annealing treatment (first homogenization treatment at 1180℃ for 24 h, then second homogenization treatment at 1200℃ for 76 h, and finally furnace cooling to 600℃), and was then air-cooled after being removed from the furnace. It was forged into bars at 1150℃, and mechanical properties were tested according to the methods in GB / T 228.1-2021 and GB / T 2039-2024. The measured room temperature tensile strength was 1214 MPa, elongation was 16.1%, 760℃ tensile strength was 832 MPa, elongation was 25.5%, and 730℃ / 550 MPa creep rupture time was 23 hours (e.g., Figures 2 to 3 (As shown).

[0095] Comparative Example 5 Comparative Example 5 is basically the same as Example 2, except that: In step ③, the steady-state melting rate during the electroslag remelting process is 4.2 kg / min.

[0096] In step ④, the steady-state melting rate during a single vacuum consumable remelting process is 5.2 kg / min.

[0097] In step ⑤, the steady-state melting rate during the secondary vacuum consumable remelting process is 6.2 kg / min.

[0098] Experimental Results: Following the methods described in HB 5220.49-2008 and HB 5220.6-2008, the GH4738 high-temperature alloy ingot prepared in this comparative example, containing 70 wt% recycled material, had a diameter of 700 mm, an O content of 10 ppm, a N content of 15 ppm, a S content of 6 ppm, and trace elements of 45 elements were less than 200 ppm. The inclusion number density was 48.72 inclusions / mm². 2 The GH4738 high-temperature alloy ingot with a diameter of 700 mm and containing 70 wt% recycled material was subjected to high-temperature homogenization diffusion annealing (first homogenization treatment at 1180℃ for 24 h, then second homogenization treatment at 1200℃ for 76 h, and finally furnace cooling to 600℃). After being removed from the furnace and air-cooled, it was forged into bars at 1150℃. Mechanical properties were tested according to the methods in GB / T 228.1-2021 and GB / T 2039-2024. The measured room temperature tensile strength was 1231 MPa, elongation was 16.9%, 760℃ tensile strength was 843 MPa, elongation was 24.9%, and 730℃ / 550 MPa creep rupture time was ≥25 hours (e.g., Figures 2 to 3 (As shown).

[0099] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-temperature alloy ingot, characterized in that, The method includes the following steps: (1) The recycled material is vacuum induction melted and cast to obtain a recycled material ingot. The chemical composition of the recycled material ingot is detected and it is cut into pieces to obtain recycled material pieces. Before vacuum induction melting, the recycled material is pretreated. The pretreatment is to treat the recycled material at high temperature in an argon atmosphere at 300~500℃ for 1~2h, cool it to room temperature, soak it in dilute hydrochloric acid with a concentration of 5~10wt% for 10~30min, and then wash it with water, perform ultrasonic treatment and dry it. (2) Vacuum induction melting of the new material stable components and C components to obtain a new material melt body. Then, power is turned off to form a film and return material blocks are added to the new material melt body for mixing and melting. Then, the chemical composition is adjusted by adding the easily oxidized components of the new material and casting is performed to obtain a vacuum induction ingot. During the mixed smelting process, rare earth metal components are also added, which are either a combination of cerium and lanthanum or a combination of cerium and yttrium; wherein the mass ratio of cerium to lanthanum is (3~5):1, and the mass ratio of cerium to yttrium is (2~5):1; the mass ratio of the rare earth metal components to the recycled material shavings is (0.00015~0.0025):

1. (3) The vacuum induction casting ingot is subjected to electroslag remelting, primary vacuum arc remelting and secondary vacuum arc remelting in sequence to obtain a high-temperature alloy casting ingot; the steady-state melting rate during the primary vacuum arc remelting process is 4.5~6.0 kg / min; the steady-state melting rate during the secondary vacuum arc remelting process is 4.1~4.5 kg / min; The amount of slag added during electroslag remelting is calculated using the following formula: In the formula, C is the amount of slag added, h is the depth of the slag pool, D is the diameter of the crystallizer, h = (1 / 2~1 / 3)×D, and γ is the density of the slag system, which is generally taken as 2400~2500 kg / m³. 3 ; The high-temperature alloy ingot contains 70% recycled material by mass, the total content of O, N, and S impurity elements in the high-temperature alloy ingot is less than 30 ppm, and the inclusion number density is less than 30 inclusions / mm². 2 The total amount of 45 trace elements in the high-temperature alloy ingot is less than 200 ppm; the diameter of the high-temperature alloy ingot is 660 mm to 700 mm.

2. The preparation method according to claim 1, characterized in that, In step (1): The vacuum induction melting process involves loading the returned material into a vacuum induction furnace, drawing a vacuum, and then melting and refining it. The refining temperature is 1500~1600℃, the refining time is not less than 30 minutes, and the vacuuming process involves drawing a vacuum until the vacuum pressure is less than or equal to 1 Pa. Prior to the casting, the recycled material melt, formed after vacuum induction melting, is passed through two slag-blocking filter channels; and / or The weight of the returned material diced is 5~10kg.

3. The preparation method according to claim 1, characterized in that, In step (2): The vacuum induction melting process involves loading the virgin material with its stable components and carbon component into a vacuum induction furnace, drawing a vacuum, and then melting and refining it. The refining temperature is 1500~1550℃, the refining time is 30~60 minutes, and the vacuuming process involves drawing a vacuum until the vacuum pressure is less than or equal to 1 Pa; and / or Before the casting is carried out, the mixed melt formed by the mixed melting is passed through two slag-blocking filter channels.

4. The preparation method according to claim 1, characterized in that, In step (3): When performing electroslag remelting, the slag system used is CaO-Al2O3-CaF2-MgO-TiO2 slag system, which contains, by mass percentage, CaO: 18~22%, Al2O3: 20~24%, CaF2: 45~55%, MgO: 4~6% and TiO2: 2~4%; The steady-state melting rate during the electroslag remelting process is 5.0~7.0 kg / min.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The high-temperature alloy ingot is a nickel-based high-temperature alloy ingot; The returned material corresponds to the returned material of nickel-based superalloys. The returned material includes block material and / or scrap. The block material includes one or more of the following: casting scrap, induction electrode riser, electroslag, consumable electrode scrap, ingot head and tail scrap, testing scrap, scrap bar stock, and scrap forging blank. The scrap includes machining turning material. The stabilizing components of the new material correspond to elements in the new material of nickel-based superalloy ingots that are not easily oxidized; and / or The easily oxidizable components of the new material correspond to the easily oxidizable elements in the new material of nickel-based high-temperature alloy ingots, excluding C.

6. A high-temperature alloy ingot prepared by any one of claims 1 to 5.

7. The application of the high-temperature alloy ingot prepared by any one of claims 1 to 5 in the preparation of bars or ring forgings.

Citation Information

Patent Citations

  • Large-size high-niobium high-temperature 706 alloy ingot and smelting process thereof

    CN111876651A

  • High-temperature alloy capable of improving use proportion of return scrap and smelting process

    CN114369736A

  • Large-size difficult-to-deform nickel-based superalloy cast ingot and preparation method thereof

    CN114657398A

  • High-temperature alloy return scrap efficient purification smelting method based on hydrogen plasma injection

    CN117965927A

  • Method for smelting K452 high-temperature alloy containing return material

    CN111621675A